The CONCEPT and ESSENCE of BUDGETING IN MODERN CONDITIONS - V. Hasanova (Publishing House of the State University of Management, 2016)
Presents arguments justifying the need of budgeting and the role of budgeting in management accounting. Dana is a contemporary approach to budgeting. The objects and subjects of budgeting. Traced the relationship of budgeting and of financial and economic activity.